Edukasi pencegahan stunting pada remaja putri serta screening haemoglobin di Dayah Insan Qurani Aceh Besar - Darmawati, Darmawati; Hadijah, Siti; Rahmayanti, Rahmayanti; Fitriana, Fitriana; Andayani, Susi (Jurnal PADE: Pengabdian & Edukasi, 2025)
Adolescent girls are future mothers who will give birth to the next generation of the nation. Currently, the government continues to promote programs aimed at reducing stunting rates to help create a "golden generation" by 2045, with adolescents being one of the primary targets. This is evident in the establishment of adolescent posyandu (integrated health service posts) as an effort to accelerate the reduction of stunting rates and to increase awareness of adolescent health. Through stunting prevention education and hemoglobin screening activities, the community service team from the Department of Medical Laboratory Technology (TLM), Poltekkes Kemenkes Aceh—consisting of lecturers and students—hopes that female adolescents at Dayah Insan Qurani will gain a better understanding of healthy lifestyles and be able to maintain their health, especially in preventing anemia caused by low hemoglobin levels. The female students and the management of Dayah Insan Qurani responded positively and showed great enthusiasm for this program. The results obtained after the activity, measured through pre-test and post-test assessments, showed an increase in knowledge about stunting prevention among adolescent girls from 58% to 94%. Hemoglobin screening results also indicated that 86% of participants had normal hemoglobin levels, with an average of 14 g/dL, while 14% had below-normal levels, averaging 10.6 g/dL, indicating the presence of anemia. The head of the madrasah at Dayah Insan Qurani, through the person in charge of the health clinic, expressed hope that similar activities will continue so that the adolescent girls at the dayah can maintain their health.